Optimizing heart failure therapy with enhanced medical management: focus on heart rate management - Hiremath, Jagdish; Kumar, Soumitra; Manoria, P. C.; Ghosh Roy, Devanshu; Koshy, A. George (International Journal of Scientific Reports, 2024)
Heart failure (HF) is a significant global health issue, affecting over 60 million people worldwide, with its prevalence expected to rise due to aging populations and the increasing incidence of comorbidities like hypertension and diabetes. Despite therapeutic advances, including quadruple therapy with renin-angiotensin-system inhibitors, beta blockers (BB), mineralocorticoid receptor antagonists, and sodium-glucose cotransporter 2 inhibitors, HF remains a condition with a poor prognosis, particularly for those with reduced ejection fraction (HFrEF), who are predominantly found in low- and middle-income countries like India. Elevated resting heart rate (HR) is a critical prognostic factor in HF, correlating strongly with cardiovascular mortality and morbidity. For every five-beat increase in HR, there is a 16% rise in cardiovascular mortality and HF hospitalization, emphasizing the need for effective HR management. However, challenges persist in optimizing HF treatment, such as the underutilization of BBs, despite their proven efficacy in reducing mortality. In India, the "double burden" of age-related and contemporary diseases complicates HF management further. Addressing unmet needs in HF care requires optimizing therapeutic strategies and improving treatment adherence, particularly in the context of HR control. Studies indicate that tailored approaches, including the use of BBs and ivabradine, could reduce HR and improve clinical outcomes. The ongoing challenges in accessing guideline-directed therapy and ensuring adherence highlight the need for comprehensive strategies to enhance patient outcomes, while personalized treatments and further research remain essential in navigating the complex landscape of HF management.